درجة تقبّل طالبات البادية الشماليّة الشرقيّة لدراسة برنامج التربية الرياضية في الجامعات الأردنية / دراسة ميدانية - العون اسماعيل سعود (Latakia University Journal - Arts and Humanities Sciences Series, 2016)
This study aimed to identify the degree of acceptance of the girl in the northeastern desert to study the physical education program in Jordanian universities. The study population consisted of all second grade students at secondary successful, and of their number (456) students, were taken from a representative sample of the random sample manner by (59.2%), for the purposes of the study, the researcher using a questionnaire to collect data. Formed resolution images of two parts: the first, and include personal information about the study sample, such as branch variable in high school, and the second: phrase that describes all the words which the degree of acceptance of the girl in the northeastern desert to study physical education program, and after data collection and discharged has consists of (15) processed using statistical methods and descriptive and analytical occasion. The study showed the following results: that the degree of acceptance of the girl in the northeastern desert to study the physical education program in Jordanian universities (medium) with a mean (3.57: 5.00), and non-existence of differences denote statistically attributable to the branch variable in the high school on the tool as a whole, and in light of the results that resulted from this study, the researcher recommended a number of recommendations. تهدف الدراسة للتعرف على درجة تقبّل طالبات البادية الشماليّة الشرقيّة لدراسة برنامج التربية الرياضية في الجامعات الأردنية / دراسة ميدانية . تكوّن مجتمع الدراسة من جميع طالبات الصف الثاني الثانوي الناجحات، والبالغ عددهنّ (456) طالبة، وقد اخذت منه عينة ممثلة للمجتمع الأصلي بطريقة العينة العشوائية بنسبة (59.2%)، ولأغراض الدراسة قام الباحث باستخدام أداة الاستبانه لجمع البيانات. تكونت الاستبانه من جزأين: الأول، ويشتمل على بيانات تهم الباحث عن عينة الدراسة مثل متغير الفرع في الثانوية العامة، والثاني: يتكون من (15) عبارة تصف كل عبارة منها درجة تقبل الفتاة في البادية الشمالية الشرقية لدراسة برنامج التربية الرياضية، وبعد جمع البيانات وتفريغها تمت معالجتها باستخدام طرق إحصائية وصفية وتحليلية مُناسبة. أظهرت الدراسة النتائج الآتية: إنَّ درجة تقبل الفتاة في البادية الشمالية الشرقية لدراسة برنامج التربية الرياضية في الجامعات الأردنية (متوسطة) بمتوسط حسابي (3.57: 5.00)، وعدم جود فروق ذات دلالة إحصائياً تُعزى إلى متغير الفرع في الثانوية العامة على الأداة ككل، وفي ضوء النتائج التي أسفرت عنها هذه الدراسة وضع الباحث عدد من المقترحات.